Center problem for generic degenerate vector fields. (January 2022) - Algaba, Antonio; Díaz, María; García, Cristóbal; Giné, Jaume
Abstract: We generalize the method of construction of an integrating factor for Abel differential equations, developed in Briskin et al. (1998), for any generic monodromic singularity. Here generic means that the vector field has not characteristic directions in the quasi-homogeneous leading term in certain coordinates. We apply this method to some degenerate differential systems.